PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PADA PERUSAHAAN OTOBUS AKAS IV PROBOLINGGO - Tumini .; Mega Dwi Pratiwi (UPT Penerbitan Universitas Jember)
The aim of this research was to determine the effect of Service Quality and Trust towards Customer Loyalty in Otobus Akas IV Probolinggo Company. The population in this study are all users of transportation services for Bus Bomel in the Company Otobus Akas IV Probolinggo about 132 people were taken samples 66 people were used as respondents in this study. Methods of data analysis used was multiple linear regression analysis. The results showed that simultaneously Quality of Service and Trust Customer Loyalty have significant effect on the Company Otobus Akas IV Probolinggo. The results of the hypothesis individual (partial) concluded that there are significant influences patially between independent variables and on dependent variables. The most dominant influence is variable Customer Loyalty Service Quality.